IDEAS OF SCIENCE AND NATURE IN BIOGRAPHIES FOR FILIPINO CHILD READERS - Christine Veloso Lao (International Journal of Humanity Studies (IJHS), 2021)
Many biographies for children are written to teach their readers social values and acceptable patterns of behavior.  But even when no such pedagogical aims are stated, biographies for children perform an ideological function. Since they narrate a “true story,” they direct young readers to think of the world and its people in the way these are presented in the text. The Bookmark Inc.’s Woman of Science Series comprises ten books, each narrating an episode in the life of a living Filipino woman scientist. The Series’ aim is to encourage more Filipino girls to consider careers in science. Its author, Didith T. Rodrigo, herself a scientist, completed writing the series through a grant from the Philippine government. Using an ecofeminist lens, I analyze the Series to answer the following questions: What political view point or interests  do these biographies serve?  What patterns of behavior do they motivate children to emulate? What social relationships , and relationships between the human and non-human, do they tend to reify?  I argue that the Series generally promotes anthropocentric views of science, consistent with Philippine policy pronouncements on science. However, tension points between this ideological frame and the words and practices of scientists featured in the series can be gleaned from the Series itself. I demonstrate how these tension points can lead to fruitful discussions on scientific practice informed by ecological understanding.